Confining Sulfur in Integrated Composite Scaffold with Highly Porous Carbon Fibers/Vanadium Nitride Arrays for High‐Performance Lithium–Sulfur Batteries. (10th January 2018) - Zhong, Yu; Chao, Dongliang; Deng, Shengjue; Zhan, Jiye; Fang, RuYi; Xia, Yang; Wang, Yadong; Wang, Xiuli; Xia, Xinhui; Tu, Jiangping
Abstract: Increasing the utilization efficiency of sulfur electrodes and suppressing the "shuttle effect" of intermediate polysulfides are the key challenge for high‐performance lithium–sulfur batteries (LSBs). Herein a facile combined strategy is reported to fabricate novel porous carbon fibers/vanadium nitride arrays (PCF/VN) composite scaffold for the storage of sulfur via a facile chemical etching united solvothermal–supercritical fluid method. More active sulfur can be stored in the PCF/VN backbone and dual blocking effects associated with "physical block and chemical absorption" for polysulfides are achieved in the PCF/VN/S integrated electrode. The PCF with highly porous structure provides large space to accommodate active sulfur and possesses cross‐linked maze channels to physically immobilize the polysulfide species. The VN nanobelt arrays demonstrate strong ability for chemically anchoring the polysulfides, thus retarding the shuttle effect. Due to the unique structure and dual confining effect, the designed PCF/VN/S electrode shows a high reversible capacity of 1310.8 mA h g −1 at 0.1 C, an extended cycle life (1052.5 mA h g −1 after 250 cycles) as well as enhanced rate capability, much better than other counterparts (CF/VN/S, PCF/S, and CF/S). This work opens a new door for fabricating high‐performance integrated electrodes for LSBs. Abstract : A novel porous carbon fibers/vanadium nitride arrays (PCF/VN) composite scaffold is demonstrated as the promising sulfur host for high‐performance Li‐S batteries. A dual polysulfides blocking strategy associated with "physical block and chemical absorption" is successfully verified in the designed PCF/VN/S electrode, which shows more effective sulfur utilization, prolonged cycling life, and enhanced high‐rate performance.